2011
DOI: 10.1111/j.1365-2702.2010.03650.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for workplace violence in clinical registered nurses in Taiwan

Abstract: For violence prevention, interventions should be sensitive to personal factors. Healthcare institutions should initiate counselling programs to help nurses cope with the stress related to workplace violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
141
4
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(192 citation statements)
references
References 26 publications
24
141
4
23
Order By: Relevance
“…Victims of violence at work in the past year had lower average age than those not exposed to violence in the last year, reinforcing findings of other studies (5,9,12,18,(20)(21) . This result can be explained from the perspective of young professionals who have less expertise in the development of their work activities and thus would have less ability to prevent attacks.…”
Section: Discussionsupporting
confidence: 79%
“…Victims of violence at work in the past year had lower average age than those not exposed to violence in the last year, reinforcing findings of other studies (5,9,12,18,(20)(21) . This result can be explained from the perspective of young professionals who have less expertise in the development of their work activities and thus would have less ability to prevent attacks.…”
Section: Discussionsupporting
confidence: 79%
“…This is in contrast to other studies in which respondents -telling the perpetrator to stop‖ or -defend physically‖ was in the range of 35-45%. 47,48 In this study, a high percentage of respondents opined that the violence was preventable and similar findings were also observed by Kumar et al in Delhi in 2016. 33 In our study, a large majority of subjects responded that making the waiting area comfortable, restricted entry to examination room and display of action under the law can be helpful in preventing the violence.…”
Section: Discussionsupporting
confidence: 76%
“…Logistic regression analysis was performed to investigate the risk factors associated with experiencing violence. The logistic regression model included variables that were identified as being P < 0.25 in any univariate analysis of the three forms of violence, and determined as being common risk factors (civil status, working time in the profession, institution and unit, average working time per week, unit where work is currently performed, status with regards to working in shifts, and the number of other personnel with whom work was performed for more than 50% of the working time) in the literature (7,(9)(10)(11) (model: Backward LR, entry: 0.05 and removal: 0.10). The level of statistical significance was accepted as P < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for not reporting were listed as the perceived futility of reporting (13,21), the inability to follow up and complete the relevant legal procedures (17), the lack of a reporting system, and the unsatisfactory responses from the superiors (21). Only one study reported that 65.4% of those subjected to mobbing reported their situation to a superior (11). The findings regarding nonreporting may be due to the perception that violence is a natural consequence of the occupation, to nurses' unwillingness to resort to jurisdiction, to their lack of confidence in professional associations, and to their inability to obtain satisfying results.…”
Section: Discussionmentioning
confidence: 99%